Healthcare Encounter and Financial Impact of COVID‐19 on Children's Hospitals. Issue 4 (17th March 2021) - Synhorst, David C; Bettenhausen, Jessica L; Hall, Matt; Thurm, Cary; Shah, Samir S; Auger, Katherine A; Williams, Derek J; Morse, Rustin; Berry, Jay G
Abstract : Children's hospitals responded to COVID‐19 by limiting nonurgent healthcare encounters, conserving personal protective equipment, and restructuring care processes to mitigate viral spread. We assessed year‐over‐year trends in healthcare encounters and hospital charges across US children's hospitals before and during the COVID‐19 pandemic. We performed a retrospective analysis, comparing healthcare encounters and inflation‐adjusted charges from 26 tertiary children's hospitals reporting to the PROSPECT database from February 1 to June 30 in 2019 (before the COVID‐19 pandemic) and 2020 (during the COVID‐19 pandemic). All children's hospitals experienced similar trends in healthcare encounters and charges during the study period. Inpatient bed‐days, emergency department visits, and surgeries were lower by a median 36%, 65%, and 77%, respectively, per hospital by the week of April 15 (the nadir) in 2020 compared with 2019. Across the study period in 2020, children's hospitals experienced a median decrease of $276 million in charges. Abstract :